Seasonal radial growth of Black pine (Pinus nigra Arnold) from Bosnia and Herzegovina, monitored by the pinning method and manual band dendrometers - Poljanšek, Simon (Acta silvae et ligni, 2019)
Despite numerous dendroclimatological investigations into different tree species from Bosnia and Herzegovina, information is lacking on intra-annual wood formation patterns, which would help us to interpret the climate signal in tree rings better. Using the pinning method and manual band dendrometers, we investigated the seasonal dynamics of radial growth of black pine (Pinus nigra Arnold) trees in two successive growing seasons: 2011 and 2012. The up to 60-year-old trees grew in a stand at the base of a hill in the western, mountainous part of the Balkan Peninsula. The seasonal dynamics of wood formation and final number of cells differed between the studied years. Wood formation started in both years in early to mid-March. Differences were noticed in the wood production culmination; in 2011 it occurred at the end of May and beginning of June in 2012 and 2011, respectively. Xylem growth finished in 2012 in the middle of August and in 2011 in the middle of September. Based on the first derivative of the Gompertz function calculated rate of xylem growth was lowest in 2011. The dendrometers recorded a slow increment rate in spring, higher in summer and a decreasing rate again in the late summer in both growing seasons. In comparison with pinning, dendrometers showed a delay in the start of radial growth of up to 20 days in 2012. Additionally, dendrometers showed an increase in stem girth after the end of both growing seasons, when wood formation was already completed. Deviations between the two methods could be ascribed to the influence of water storage dynamics in the main stem and numerous structural processes in bark tissue, which are captured in dendrometer data. The influence of weather conditions on xylem phenology is also indicated by differences between the two studied years, although it is difficult to identify the influence of particular short-term weather events.
Keywords: Balkan Peninsula; Balkanski polotok; cambium; debelinska rast; kambij; manual dendrometers; metoda pining; pinning; Pinus nigra; radial growth; ročni dendrometri